WOMEN FARMERS RESPOND ABOUT RICE BARN VILLAGE PROGRAM IN THE PAMOTAN VILLAGE, DAMPIT SUBDISTRICT, MALANG REGENCY - Prayoga, Kadhung; Yuliati, Yayuk (HABITAT, 2015)
Malang District was one of the recipients of the Village Food Barn Program because as rice production centre in East Java Province and the majority of the population work as farmers. On food barn village program implementation in Malang District is not only involves men farmers but also include women farmers participation. This research aims to analyse whether there is influence among knowledge, attitude and skill against the formation of women farmersâ response on food barn village in Pamotan Village, Dampit Subdistrict, Malang Regency. Women farmers to be sampled in this research, determination of sample do with non-probability approach and using purposive sampling methods by as much as 45 respondents. The analysis includes descriptive analysis, scoring with likert scale, and path analysis (Structural Equation Modelling). Results of the analysis show that variable knowledge turns out to affect positively against the response variables. Although its influence is indirect effect and no direct effect against the response with the value of indirect effect is 0.041. The attitude variable influences are directly and positively to the establishment of a response and the value is 1.18. Means that each an increase in attitude, it will increase the formation of a response by 1.18. Skill variable is directly affecting for establishment the response but it has negative values and the value is -0.30. Means that every single increase in skill, it will reduce establishment of the response of 0.30.Â